EL FINAL DEL BIPARTIDISMO EN COSTA RICA: UN RETRATO ELECTORAL 1994-2002 - Rodríguez, Florisabel; Espinosa, Rowland; Madrigal Pana, Johnny (Universidad de Costa Rica, 2005)
This article describes the end of bipartidism in Costa Rica. The analysis is done bothgeographically and socially, based on presidential electoral returns of 1994, 1998 and2000, and the 2000 Population Census. The unit of analysis is the district, for thepolitical parties Unidad Social Cristiana (PUSC) y Liberación Nacional (PLN).